Enfermagem : suas percepções e o uso de psicotrópicos em tempos de pandemia - Bouret, Andréa Luiza de Carvalho (2022)
This study presents a brief analysis of professional nurses and the stereotypes attributed to these throughout their history, through social markers, they present the profile of these professionals in a city in Mato Grosso, I take advantage of this study to understand the transformations of their daily life due to the Covid19 pandemic and whether these factors, pandemic and profession, contributed to and the use of psychotropic drugs during their professional careers. Objectives: Understand the historical context that influenced the construction of their professional nursing identity, identify the main problems encountered by them as a result of coping with COVID19 and understand if there was a need for the drug use of psychotropic drugs due to the difficulties faced in this pandemic context. Method: Fieldwork for development was carried out before the pandemic in health facilities and during the pandemic period through video call, through the whatsapp program. This approach was appropriate to the need for social distancing and the difficulty in accessing health facilities due to the high transmissivity of the virus and lack of knowledge about the disease.